Determinación de la resistencia y resistividad eléctrica de probetas de varíos diseños de hormigón sometidas a ataques de contaminantes - Mejía Orellana, Vicky (2010)
This graduation project consists in determinate the concrete electricity resistivity in order to know its behavior and the protection that give to the rods. Resistivity is affected by different corrosives ambient. It is study the necessary basic theory for this project realization, like the used material properties, diverse techniques and the medium that affected the concrete properties, also the detail for the equipments that were employed The diverse concrete tests elaboration procedure its detailed, two types pozzolanic and portland type II, and the different ambient in them were exposed, carbonation camera, submerge in sodium chloride and normal conditions. The obtaining of cell factor is explained, this is an important data for this project. With all the information and results the graphics are obtaining. Obtaining results are analyzed, considered that the resistance measures were realized periodic each 15 days, during 6 months, as an important topic for this project it is realized a resistivity comparative evaluation between the both concretes pozzolanic and Portland type II. The conclusions and recommendations are presented at the end for this project.